Measuring Intention to Use on Spotify Users in Samarinda City - Suminto Suminto; Dyah Kusrihandayani; Kristin Wulansari; Dewi Anriani (International Journal Labs, 2023)
This study aims to analyze and prove the effect of ewom, social influence, perceived enjoyment on attitude and ewom, social influence and perceived enjoyment on intention to use, and attitude on intention to use Spotify application users in Samarinda City. A total of 102 samples were used in this study, respondents were Spotify users in Samarinda City who were taken offline with a Likert scale of 1-5. Validity and reliability tests were carried out using IBM SPSS Statistics 23 software and estimation tests and structural model fit tests were carried out using IBM AMOS software. The test results show ewom, social influence and perceived enjoyment have a significant positive effect on attitude. Ewom has no significant negative effect on intention to use. Meanwhile, social influence and perceived enjoyment have an insignificant positive effect on intention to use and attitude has a significant positive effect on intention to use.